Analisis Tax Avoidance, Firm Size Dan Good Corporate Governance Terhadap Cost Of Capital (Study Empiris Pada Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di Bei Tahun 2016-2019) - Nur Halimatus Sa’diyah; Jeni Susyanti; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to partially see the effect of Tax Avoidance, Firm Size and Good Corporate Governance on the Cost of Capital. The population in this study are all food and beverage subsector companies listed on the Indonesia Stock Exchange for the period of 2016-2019. The sample of this study used a purposive sampling technique. From the population of 26 companies, 9 companies were obtained as samples with a research period of four years (2016-2019). The data analysis technique used is multiple linear regression analysis. Based on the results of the study indicate that Tax Avoidance has a negative effect on the Cost of Capital, Firm Size does not affect the Cost of Capital and Good Corporate Governance does not affect the Cost of Capital.Keywords : Tax Avoidance, Firm Size, Good Corporate Governance, Cost of Capital.